Over a decade of successful treatment with tocilizumab in a maintenance hemodialysis patient for Castleman disease: a case report and literature review - Aya Shima; Takahiro Shima; Chie Matsuo; Takaichi Suehiro; Tomohiko Kamimura; Hiroaki Niiro; Makoto Hirakawa (Renal Replacement Therapy)
Abstract Background Castleman disease (CD) is a rare, non-neoplastic lymphoproliferative disorder with characteristic histopathological features in lymph nodes. The clinical presentation of CD is highly variable, which can complicate both diagnosis and treatment. Tocilizumab, an interleukin-6 receptor antibody, is approved for the treatment of CD, but there is limited data regarding its use, efficacy, and safety in patients undergoing maintenance hemodialysis. Case presentation We present the case of a 53-year-old woman with CD who has been successfully and safely treated with tocilizumab for over 10 years, while on maintenance hemodialysis. Initially, at the age of 48 years, the patient presented with anemia and renal impairment, leading to a diagnosis of CD after an inguinal lymph node biopsy. Treatment with prednisolone was initiated, but poor compliance led to discontinuation of follow-up. At the age of 53 years, she returned with severe renal dysfunction (serum creatinine 7.16 mg/dL) and profound anemia (hemoglobin 4.0 g/dL), necessitating initiation of hemodialysis and erythropoiesis-stimulating agents. Despite these interventions, her anemia persisted. Additional findings of residual lymphadenopathy, polyclonal hypergammaglobulinemia, and elevated C-reactive protein (CRP) levels indicated that her anemia was likely attributable to CD. As a result, tocilizumab therapy was initiated, leading to rapid improvement in both anemia and CRP levels. Although her renal function did not recover, and she remained dialysis-dependent, the patient has continued to receive tocilizumab for over a decade without major adverse events, and has achieved stable disease control. Conclusions This case highlights the successful long-term management of CD with tocilizumab in a patient on maintenance hemodialysis. It underscores the potential for tocilizumab to provide sustained disease control and symptom relief in CD, even in the setting of renal failure and hemodialysis. Further research is needed to evaluate the safety and efficacy of tocilizumab in this patient population.